2013
DOI: 10.1007/s00210-013-0908-6
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of dexpanthenol on bleomycin-induced pulmonary fibrosis in rats

Abstract: Despite extensive studies, there is no effective treatment currently available other than pirfenidone for idiopathic pulmonary fibrosis. A protective effect of pantothenic acid and its derivatives on cell damage produced by oxygen radicals has been reported, but it has not been tested in bleomycin (BLM)--induced pulmonary fibrosis in rats. Therefore, we aimed to investigate the preventive effect of dexpanthenol (Dxp) on pulmonary fibrosis. Thirty-two rats were assigned to four groups as follows: (1) control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 38 publications
3
24
0
Order By: Relevance
“…The elevation in the levels of glycoprotein components as observed in the study on BLM induction may be due to the secretion of cell membrane glycoconjugates into the circulation 14,36,40 and may also be due to increased deposition of macromolecular components, which may be a physiological adjustment to the pathological process. Elevated levels of glycoprotein components have been already reported during pulmonary fibrosis 14,16,36,43 Natural antioxidants, such as polyphenols from green tea extracts are known for their capability of reducing the expression of ECM genes 44 .…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…The elevation in the levels of glycoprotein components as observed in the study on BLM induction may be due to the secretion of cell membrane glycoconjugates into the circulation 14,36,40 and may also be due to increased deposition of macromolecular components, which may be a physiological adjustment to the pathological process. Elevated levels of glycoprotein components have been already reported during pulmonary fibrosis 14,16,36,43 Natural antioxidants, such as polyphenols from green tea extracts are known for their capability of reducing the expression of ECM genes 44 .…”
Section: Resultsmentioning
confidence: 89%
“…Lung inflammation is considered to be a major contributing factor in the induction of pulmonary fibrosis 14,15,33 . ROS such as superoxide anion, hydrogen peroxide, and hydroxyl radical are reported as mediators of lung inflammatory processes 33 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Those in Groups 2 and 4 were treated with Dxp (Bepanthene ampul®, 500 mg, Bayer Corp., Istanbul, Turkey) and were administered once a day by IP injection at a dose of 500 mg/kg of body weight, starting from birth until postnatal day four. The dosage of Dxp was chosen based on the previous studies which have been reported to cause marked antioxidative effects in rats [18,19].…”
Section: Nec Procedures and Dxp Applicationmentioning
confidence: 99%